THE EFFECT OF FINANCING, HUMAN RESOURCE QUALITY, AND MARKETING ON MSME INCOME WITH BUSINESS DEVELOPMENT AS A MODERATING VARIABLE (A STUDY OF BSI CUSTOMERS IN KEDATON BANDAR LAMPUNG) - Rizki, Marisa; Anggraeni, Erike; Ridwansyah, Ridwansyah (Ad Deenar: Jurnal Ekonomi dan Bisnis Islam, 2026)
The increase in income of Micro, Small, and Medium Enterprises (MSMEs) is an important factor in supporting regional economic growth and poverty alleviation. However, MSMEs still face various challenges, such as limited access to financing, low quality of human resources (HR), and suboptimal marketing strategies. This study aims to analyze the effect of financing, HR quality, and marketing on MSME income, with business development assistance as a moderating variable. The research employs a quantitative approach using a survey method targeting MSME actors who are customers of Bank Syariah Indonesia (BSI) in Bandar Lampung City and who participated in development assistance programs during the 2020–2024 period. Data were collected through questionnaires and analyzed using Moderated Regression Analysis (MRA) to examine both direct effects and moderating effects among variables. The results indicate that financing, HR quality, and marketing have a positive and significant effect on MSME income. Furthermore, development assistance is proven to strengthen the influence of financing, HR quality, and marketing on MSME income. These findings emphasize that sustainable development assistance plays a strategic role in optimizing the utilization of Islamic financing, enhancing human resource capacity, and improving marketing effectiveness to increase MSME performance and competitiveness.